2021
DOI: 10.1007/s11269-021-03021-z
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the Impact of Landuse/Landcover Change and Climate Change on Runoff in the Upstream Area of the Yangtze River, China

Abstract: Landuse/landcover change (LULCC) and climate change (CC) impacts on streamflow in high elevated catchments are very important for sustainable management of water resources and ecological developments. In this research, a statistical technique was used in combination with the Soil and Water Assessment Tool (SWAT) to the Upstream Area of the Yangtze River (UAYR). Different performance criteria (e.g., R 2 , NSE, and PBIAS) were used to evaluate the acceptability of the model simulation results. The model provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Ensuring land management systems that maintain land cover is critical to sustaining human livelihoods in Africa [58]. LULC variation is one of the important factors affecting runoff in high-altitude catchment areas, which is of great significance for sustainable management and ecological development of water resources [59]. Therefore, the accuracy of land cover data will affect the indicators corresponding to the sustainable development goals [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring land management systems that maintain land cover is critical to sustaining human livelihoods in Africa [58]. LULC variation is one of the important factors affecting runoff in high-altitude catchment areas, which is of great significance for sustainable management and ecological development of water resources [59]. Therefore, the accuracy of land cover data will affect the indicators corresponding to the sustainable development goals [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The average elevation of YRSR is 4500 m above sea level, and it is located between longitudes 90 50 N. The YRSR catchment area is 137,000 km 2 , which is 7.6% of the total area of the Yangtze River Basin and it contributed 20% to the total volume of water of Yangtze River Basin. The dominant land-cover types are natural forests, glaciers, wetlands, natural lakes, and permanently and seasonally frozen grounds [42][43][44][45][46][47]. The catchment area's climate is subtropical monsoon, and historical records showed that it has been getting warmer since 1989 due to an increase in temperature [41].…”
Section: Catchment Areamentioning
confidence: 99%
“…According to Pruski et al (2015) and Yoon et al (2010), pollutants accumulate in urban basins during dry weather, being produced not only by human activity but also by atmospheric deposition. The first rapid contribution when rain occurs after a period of drought consists of removing pollutants from impermeable surfaces, providing them highly concentrated in wastewater (Ahmed et al, 2022).…”
Section: Introductionmentioning
confidence: 99%